Notes from the mainstage: World Agri-Tech innovation summit San Francisco, March 2024 - Steele, Megan (2024)
As part of the ongoing effort led by the Partnerships & Communication team at the Alliance of Bioversity International and CIAT to engage more systematically and creatively with the private sector and non-traditional partners, the Accelerate for Impact Platform attended the World Agri-Tech Innovation Summit in San Francisco: an innovation summit held in strategic locations across the globe to engage key innovation ecosystems and strengthen agri-food technologies by connecting the relevant players such as startups pioneering emerging technologies, strategics/corporates, impact investors including venture capital funds, accelerators and more. For each Mainstage session from the March 2024 event, a handful of key themes of discussion are identified. Disclosure: Note-taking was performed originally by A4IP team members, then summarized and organized utilizing ChatGPT